Foreword - Ghiorghita, Eugen (Journal of Economic Development, Environment and People, 2015)
Society today is in transition. We can see it. We live in it. Actually, the mankind’s history is a transition: from simple to complex, from primitivism to civilization. There has been a permanent change in ideas, mentalities, knowledge, institutions and technologies....